Factors Influencing Requirement's Implementation of Clinical Dental Student of Muhammadiyah University of Yogyakarta - Wahyu Safitri Dhini Putranti; Iwan Dewanto; Indri Kurniasih; Novitasari Ratna Astuti (Journal of Indonesian Dental Association, 2018)
Introduction: Institution of Dentist Education (IPDG) which requires professional students to meet a number of requirements tend to get constraints, such as delay in graduation due to students unable to meet all the requirements. This constraint relates to important factors in professional education, namely lecturer factor, patient factor, and student factor. Objectives: This study aimed to understand the factors that influence the fulfillment of the requirements of clinical dental students of Muhammadiyah University of Yogyakarta (UMY). Methods: This research was an observational research with cross sectional design. Research subjects amounted to 100, taken by purposive sampling technique. Research data consisted of primary and secondary data. Primary data were obtained from answers to questionnaires and secondary data were obtained from reports management information system in dental and mouth hospital of UMY. Research data were analyzed by Pearson correlation and multiple linear regression. Results: There was a difference between the questionnaire answers and the reports of management information system regarding the fulfillment of the requirements. Pearson correlation analysis results obtained significance value of the three factors of 0.000 (p<0.05). The result of multiple linear regression analysis showed that lecturer factor had significance value 0.003 (p<0.05), patient factor had significance value equal to 0.013 (p<0.05), and student factor had significance value equal to 0.001 (p<0.05). Simultaneously factor of lecturer, patient factor, and student factor significantly influence to fulfill requirement of clinical dental student with F count equal to 24.836 and significance number 0.000. The contribution of these three factors had an influence of 41.9%, the remaining 58.1% was determined by other variables that were not in this study. Conclusion: Lecturer factor, patient factor, and student factor have relevance and influence the fulfillment of the requirements of clinical dental students of UMY.